2022
DOI: 10.5455/javar.2022.i597
|View full text |Cite
|
Sign up to set email alerts
|

Fowl typhoid live lyophilized vaccine applied at 3-month intervals protected layer chickens from Salmonella gallinarum infection and prevented cloacal shedding

Abstract: Objective: Here, we developed and tested the efficacy of a vaccination protocol based on a commercially available live attenuated Salmonella enterica serovar Gallinarum (Salmonella galli¬narum) in layer chickens. Materials and Methods: 50 layer chickens of 16 weeks age were obtained and divided into two groups (n = 25), control and vaccinated. The vaccinated group received Salmonella vaccine at 0.2 ml/bird, s/c route at 16, 18, 30, and 42 weeks of age. At 21 weeks of age, birds from both groups were challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…The histopathological examination of spleen, thymus, and bursa of Fabricius in our study indicated lymphocytic depletion and congestion in the S. gallinarum infected birds which also endorsed by a previous in vivo study [66]. The histological sections of spleen, thymus and bursa of Fabricius showed lymphocytic depletion and congestion which is in line with the previous studies [67][68][69].…”
Section: A C C E P T E Dsupporting
confidence: 92%
“…The histopathological examination of spleen, thymus, and bursa of Fabricius in our study indicated lymphocytic depletion and congestion in the S. gallinarum infected birds which also endorsed by a previous in vivo study [66]. The histological sections of spleen, thymus and bursa of Fabricius showed lymphocytic depletion and congestion which is in line with the previous studies [67][68][69].…”
Section: A C C E P T E Dsupporting
confidence: 92%
“…Nevertheless, live vaccines are adventitious i.e., more effective, and have additional protective effects when administered orally by increasing lymphocyte proliferation (Hajam et al, 2018). Recently, Akter et al (2022) used SG-9R Strain owl typhoid live lyophilized vaccine (Komipharma, South Korea) and reported 100% clinical protection and reduced the Salmonella shedding in the feces and eggs of the challenged birds.…”
Section: Figmentioning
confidence: 99%